Games-Based Needs Analysis of Futsal Skill Exercise for Junior High School Student (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
Futsal is a game that is almost the same as football in general, but some basic techniques are different from football, especially for the young player. They need a fun game and it is easy to understand without written theory. This study aimed to know the needs analysis of the games-based model of futsal skill exercise for Junior High School student. The method used a descriptive qualitative method. The process of collecting data used observation, interview, and questionnaires. The result of the analysis shows that there is no standard guide and less variation of games in futsal playing. The exercise is still conventional. Students need basic techniques to play futsal through the principles of exercise using a variety of games and the correctness of good motion.